AAV2/1-TNFR:Fc Gene Delivery Prevents Periodontal Disease Progression - Cirelli, Joni A (2008)
Periodontal disease is a chronic inflammatory condition induced by tooth-associated microbial biofilms that induce a host immune response. Therapeutic control of progressive tissue destruction in high-risk patients is a significant challenge in therapy. Soluble protein delivery of antagonists to tumor necrosis factor alpha (TNF-α) inhibits alveolar bone resorption due to periodontitis. However, protein therapy raises several concerns, such as recurrence of disease activity after treatment cessation and repeated dosing regimens. In this study, we used pseudotyped adeno-associated virus vector based on serotype 1 (AAV2/1) to deliver the TNF receptor-immunoglobulin Fc (TNFR:Fc) fusion gene to rats subjected to experimental Porphyromonas gingivalis (Pg)-lipopolysaccharide (LPS)-mediated bone loss. Animals received Pg-LPS delivered to the gingivae thrice weekly for 8 weeks, vehicle alone, Pg-LPS and intramuscular delivery of pseudotyped AAV2/1-TNFR:Fc vector (1×10(11) DNase I-resistant particles) or AAV2/1-TNFR:Fc vector delivered to naïve animals. AAV2/1-TNFR:Fc therapy led to sustained therapeutic levels of serum TNFR protein and protected against Pg-LPS-mediated loss of bone volume and density. Furthermore, AAV2/1-TNFR:Fc administration reduced local levels of multiple pro-inflammatory cytokines and osteoclast-like cells at the periodontal lesions. These findings suggest that delivery of AAV2/1-TNFR:Fc may be a viable approach to modulate periodontal disease progression.